2008
DOI: 10.1007/s00221-008-1355-3
|View full text |Cite
|
Sign up to set email alerts
|

The statistics of natural hand movements

Abstract: Humans constantly use their hands to interact with the environment and they engage spontaneously in a wide variety of manual activities during everyday life. In contrast, laboratorybased studies of hand function have used a limited range of predefined tasks. The natural movements made by the hand during everyday life have thus received little attention. Here, we developed a portable recording device that can be worn by subjects to track movements of their right hand as they go about their daily routine outside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

39
268
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(313 citation statements)
references
References 39 publications
(68 reference statements)
39
268
3
3
Order By: Relevance
“…Previous mental rotation studies have only paid little attention to the role of the thumb as a special digit of the human hand. This is surprising, given the special role of the thumb in human hand anatomy and hand function [e.g., 6,7,8,15]. Several studies pointed towards the significance of the thumb as asymmetry marker in handedness tasks if visual strategies are applied [e.g., 19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous mental rotation studies have only paid little attention to the role of the thumb as a special digit of the human hand. This is surprising, given the special role of the thumb in human hand anatomy and hand function [e.g., 6,7,8,15]. Several studies pointed towards the significance of the thumb as asymmetry marker in handedness tasks if visual strategies are applied [e.g., 19,20].…”
Section: Introductionmentioning
confidence: 99%
“…They found a strong relationship between the two structures with better performance when both match. While it has been shown that human fingers have separable DOF [6], 3D manipulation is inherently an integral task [7]. The thumb, index and middle fingers can be moved e-mail: anthony.martinet@lifl.fr e-mail: gery.casiez@lifl.fr e-mail: laurent.grisoni@lifl.fr separately from one another while users perceive the attributes of 3D objects (position and orientation) as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the separable structure of fingers [6], it appears impossible to exactly match the perceptual structure of the task with the control structure of multi-touch displays. The previous work above shows there is no clear answer to this problem.…”
Section: Introducing Ds3mentioning
confidence: 99%
“…Adopting the representation used in [10], the articulation of the human hand can be described by 20 parameters encoding the angles of the human hand joints and thus forming a 20-dimensional space. However, only a fraction of this space contains valid hand configurations [6,17]. For example, if no external forces are applied, the range of motions that can be performed by each finger joint is limited [9].…”
Section: Introductionmentioning
confidence: 99%